Estado nutricional e características socioeconômicas e de saúde de crianças filhas de mulheres haitianas em Cuiabá MT - Batista, Delma Riane Rebouças (2017)
Childhood growth and development have important repercussions on the individual's future life, and many factors can directly influence this phase of life. The immigrant status in our country may be related to the determinants and determinants of the child's health, such as low socioeconomic status of the family, lack of access to basic services and inadequate food. Parallel to the increase in the number of Haitian immigrants of productive age in Brazil, there are children who accompany their parents in this new stage, or even children who were born in Brazil, however, few studies have been found on this topic. In this sense, the present study aims to analyze the demographic, socioeconomic and obstetric characteristics and its association with body mass index and height for the age of children under five years old, daughters of Haitian women residing in Cuiabá-MT. This is a cross-sectional, census-based study. The data were collected through an interview by a bilingual interviewer, with information about the socioeconomic conditions of the family, the mother's gestational history, prenatal care, delivery and postpartum referring to the child and health / illness history of the child. Anthropometric data of the child were also collected, and the body mass index (BMI) for age and height for age was analyzed, adopting the z-score for analysis and classification, according to sex and age of the child. Frequency distributions, measures of central tendency and dispersion of the variables of interest were calculated. The anthropometric indicators (BMI and height for age) were tested by the Kolmogorov-Smirnov test and, with a parametric distribution, Student's T-test or ANOVA were used to test significant differences of means between the groups, considering the level of significance of 5%. Data were analyzed using the SPSS program, version 17. Sixtyseven children, 73.2% with up to 24 months of age and 34.3% of males were evaluated. Only 2 children (2.98%) presented BMI for age less than -2 z score (thinness) and no children were classified as overweight (> 2 z score), nor were they short for age (<-2 z score ). It was observed a significant proportion of families with per capita incomes less than 1/4 of minimum wage (65.6%), without home follow-up by the ESF (88.1%) and high working hours of the mothers (43.3%). There was an association between the onset of prenatal care until the third month of gestation and the female with the highest mean BMI for age. Regarding the height-for-age index, an association with lower mean values was found for households with more than one inhabitant per room, higher age group (> 24 months) and daily child care (morning and afternoon). The results of the present study made it possible to know the socioeconomic profile as well as the basic health conditions of the children descendants of Haitian women in CuiabáMT. These data point to the precarious socioeconomic conditions of this population and that the nutritional status of these children is similar to those of low-income Brazilian children and better than those of the same age group residing in Haiti.